Performance in hypoxia inducing environments: Natural and simulated altitude - Pedlar, C.; Whyte, G.; Kreindler, J.; Hardman, S.; Levine, B. (The Sport and Exercise Scientist, 2011)
• Altitude training offers a natural method of potentially enhancing performance. • Individuals should be assessed and educated on the effects of altitude before travelling. • Pre-acclimation is recommended prior to travel to moderate and high altitude to reduce training disruption in athletes and AMS in climbers. • Disrupted training and recovery are expected at altitude, requiring careful management. • At high altitude, AMS is common, potentially worsening to HAPE or HACE, all of which should be assessed and treated by a doctor. If no doctor is present, individuals travelling to high altitude should be educated in the signs, symptoms and treatment of AMS. • Other problems such as sunburn and dehydration should be avoided.